Provincial globalization in India
1 online resource (210 pages)
Keywords: The movement of people from small towns and villages of India to places outside the country raises a number of questions– about the networks that enable their mobility, the aspirations that motivate them, what they give back to their home regions, and how their provincial home worlds engage with and absorb the consequenttransnational flows of money, ideas, influence and care.